2017
DOI: 10.1126/science.aal0157
|View full text |Cite
|
Sign up to set email alerts
|

Persistent effects of pre-Columbian plant domestication on Amazonian forest composition

Abstract: The extent to which pre-Columbian societies altered Amazonian landscapes is hotly debated. We performed a basin-wide analysis of pre-Columbian impacts on Amazonian forests by overlaying known archaeological sites in Amazonia with the distributions and abundances of 85 woody species domesticated by pre-Columbian peoples. Domesticated species are five times more likely than nondomesticated species to be hyperdominant. Across the basin, the relative abundance and richness of domesticated species increase in fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
401
0
64

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 516 publications
(486 citation statements)
references
References 67 publications
21
401
0
64
Order By: Relevance
“…Our results are also consistent with the hypothesis suggested that hyperdominant plants in Amazonia, such as M. flexuosa , correlate with their proximity to pre‐Columbian archeological sites, and that plant populations of economically important species are maintained preferentially along river margins (Levis et al., 2017). Furthermore, as humans increasingly hunted large vertebrates in forests typically far from the water (Peres, Emilio, Schietti, Desmoulière, & Levi, 2016), animal‐dependent seed dispersal of M. flexuosa decreased in those areas, resulting in lower gene flow, all the while maintained closer to rivers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are also consistent with the hypothesis suggested that hyperdominant plants in Amazonia, such as M. flexuosa , correlate with their proximity to pre‐Columbian archeological sites, and that plant populations of economically important species are maintained preferentially along river margins (Levis et al., 2017). Furthermore, as humans increasingly hunted large vertebrates in forests typically far from the water (Peres, Emilio, Schietti, Desmoulière, & Levi, 2016), animal‐dependent seed dispersal of M. flexuosa decreased in those areas, resulting in lower gene flow, all the while maintained closer to rivers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as humans increasingly hunted large vertebrates in forests typically far from the water (Peres, Emilio, Schietti, Desmoulière, & Levi, 2016), animal‐dependent seed dispersal of M. flexuosa decreased in those areas, resulting in lower gene flow, all the while maintained closer to rivers. Although these observations remain to be tested explicitly, our patterns of high diversity are also consistent with the hypothesis that large population sizes of this species have been maintained by continuous activities of human cultivation, likely for thousands of years (Levis et al., 2017). As a result, outcrossing would be favored by human tending and a high number of reproductive individuals would be maintained, resulting in a higher effective population size and thus higher genetic variation (Frankham, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in part a result of limited archaeological survey and exploration of tropical forests relative to other environments. It is also due to the fact that few ecologists and conservationists have engaged with mounting evidence for the long-term human impact of tropical forest environments (however, see 15,31,102 ).…”
Section: The Deep History Of Global Tropical Forests: Implications Fomentioning
confidence: 99%
“…Accordingly, scholarly assumptions about the timing of significant anthropogenic impacts on tropical forests generally point to the post-industrial era or, at the earliest, the colonial era of European 'discovery' [26][27] . Clearly, the accumulating database of archaeological and palaeoecological evidence for pre-industrial and pre-colonial tropical forest occupation and transformation has not been effectively communicated beyond a restricted set of sub-disciplines (though see [28][29][30][31] ). As a consequence, this evidence has only played a small role in discussions about the start date or characteristics of the Anthropocene (e.g.…”
Section: Introductionmentioning
confidence: 99%